1996
DOI: 10.1007/s004410050528
|View full text |Cite
|
Sign up to set email alerts
|

Culture of endothelial cells from human placental microvessels

Abstract: Endothelial cells are known to participate in angiogenesis, adaptation of vascular tonus and maintenance of blood fluidity in the microcirculation. To investigate these functions in the placenta, we devised a method of isolation and culture of endothelial cells from villous microvessels. In primary culture, these intraplacental endothelial cells exhibited many features observed in microvascular endothelium from other organs: spindle-shape, rosette associations, circular arrangements and confluence. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These circular structures were also observed in brain MEC cultured on Matrigel (Gerhart et al 1988). The MEC were stained by the von Willebrand factor reaction and took up fluorescent acetylated low-density lipoproteins (Kacemi et al 1996). There was no evidence for contaminating cells exhibiting a pericyte phenotype or actin stress fibers as we have previously described using the placenta (Kacemi et al 1996) or as shown by others with the brain (Rupnick et al 1988;Abbott et al 1992).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…These circular structures were also observed in brain MEC cultured on Matrigel (Gerhart et al 1988). The MEC were stained by the von Willebrand factor reaction and took up fluorescent acetylated low-density lipoproteins (Kacemi et al 1996). There was no evidence for contaminating cells exhibiting a pericyte phenotype or actin stress fibers as we have previously described using the placenta (Kacemi et al 1996) or as shown by others with the brain (Rupnick et al 1988;Abbott et al 1992).…”
Section: Discussionmentioning
confidence: 90%
“…The MEC were stained by the von Willebrand factor reaction and took up fluorescent acetylated low-density lipoproteins (Kacemi et al 1996). There was no evidence for contaminating cells exhibiting a pericyte phenotype or actin stress fibers as we have previously described using the placenta (Kacemi et al 1996) or as shown by others with the brain (Rupnick et al 1988;Abbott et al 1992). MEC might modify their phenotype according to the matrix components such as collagen, laminin (Kubota et al 1988) or Matrigel (Kubota et al 1988Gerhart et al 1988).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations